Giving Mung Bean Extract on Changes in Preconception Mothers' Hemoglobin Levels at the Blue Telaga Community Health Center - Hiola, Fidyawati Aprianti A.; Ishak, Fifi; Mulyaningsih, Sri; Zakaria, Fatmah (Journal La Medihealtico, 2025)
This study aims to determine the effect of giving green bean juice on changes in hemoglobin levels in preconception mothers at the Danau Biru Health Center. This study used a pre-experimental design with one group pre-post test design. The sample used was a purposive sampling method with a sample size of 26 respondents. Data collection using observation sheets and data analysis using the Independent Sample T Test analysis with a significance level of 95% (α = 0.05), obtained a p value = 0.013 and a static tick test through a significance level of 95% IK value of 10.9 which means that giving green bean juice is 10.20 times more likely to increase hemoglobin levels, so it can be concluded that there is an effect of giving green bean juice on changes in hemoglobin levels in preconception mothers. This study was conducted to help preconception mothers in dealing with pregnancy and to increase knowledge about Hb.